Comparison of two types of xenogeneic matrices to treat single gingival recessions: A randomized clinical trial - Santamaria, Mauro Pedrine [UNESP] (2021)
Background: Xenogeneic matrices (XMs) have been increasingly used for root coverage procedures. This study compared the use of two types of XM (collagen matrix [CM] and xenogeneic acellular dermal matrix [XDM]) associated with the coronally advanced flap technique (CAF) to treat single gingival recessions. Methods: Seventy-five patients presenting single RT1 gingival recession were treated by CAF (control group, n = 25), CAF+CM (test group 1, n = 25), or CAF+XDM (test group 2, n = 25) and completed 6-month follow-up. Clinical, patient-centered, and esthetic assessments were performed and intra- and intergroup differences were analyzed. Results: At 6 months, the mean recession reduction for CAF, CAF+CM, and CAF+XDM was 2.4 ± 0.8 mm, 2.4 ± 0.9 mm and 2.1 ± 0.8 mm, respectively (P > 0.05). The corresponding mean percentage of root coverage was 78.9% ± 26.2% for CAF, 78.0% ± 28.5% for CAF+CM, and 65.6% ± 26.9% for CAF+XDM (P > 0.05). Dentin hypersensitivity and esthetic conditions showed significantly improvements in all groups. Test groups presented significant gains in gingival thickness (GT; CAF+CM: 0.4 ± 0.3 mm; CAF+XDM: 0.4 ± 0.2 mm) compared to the control group (CAF: 0.0 ± 0.1 mm; P < 0.05). Conclusion: The CAF, CAF+CM, and CAF+XDM treatments each provided similar results in the treatment of single gingival recessions. The addition of either CM or XDM to CAF increases the GT.